Characterization of leptospira interrogans serovar pomona isolated from swine in Brazil - Miraglia, Fabiana; Moreno, Luisa Zanolli; Morais, Zenaide Maria; Langoni, Helio; Shimabukuro, Fabio Hiroto; Dellagostin, Odir Antonio; Hartskeerl, Rudy; Vasconcellos, Sflvio Arruda; Moreno, Andrea Micke (Journal of Infection in Developing Countries, 2015)
Introduction: Leptospira interrogans swine infection is a cause of serious economic loss and a potential human health hazard. In Brazil, the most common serovars associated with swine infections are Pomona, Icterohaemorrhagie and Tarassovi. Cross-reactions among serovars and the failure of infected animals to seroconvert may complicate the interpretation of serological tests. Molecular methods with better discriminatory powers are useful tools for swine leptospirosis characterization and diagnosis. Methodology: This study evaluated nine L. interrogans isolates from the States of Sao Paulo and Minas Gerais during different time periods. Isolates from diseased and apparently healthy swine were characterized by microscopic agglutination tests with polyclonal antibodies and were genotyped by VNTR, PFGE and MLST techniques. Broth microdilution was used to determine the minimal inhibitory concentration of the antimicrobials of veterinary interest. Results: The strains were identified as L. interrogans serogroup Pomona serovar Pomona Genotype A, while MLST grouped all of the isolates in sequence type 37. The PFGE analysis resulted in two pulsotypes with more than 70% similarity, distinguishing serovar Pomona isolates from the serovar Kennewicki reference strain. All of the isolates presented low MIC values to penicillin, ampicillin, ceftiofur and tulathromycin. High MIC values for fluoroquinolones, tiamulin, gentamicin, tetracyclines, neomycin, tilmicosin and sulfas were also observed. Conclusions: All molecular techniques were concordant in L. interrogans serovar Pomona identification. This serovar may have a different antibiotic susceptibility profile than previously reported for Leptospira isolates.
Keywords: Antimicrobial resistance; Leptospira interrogans; MLST; PFGE; Serovar Pomona